2017
DOI: 10.13075/ijomeh.1896.01076
|View full text |Cite
|
Sign up to set email alerts
|

Activity of daily living on non-working and working days in Polish urban society

Abstract: Objectives: Activities of daily living are currently the simplest form of activity. For many people this is the only activity in which they participate. In this connection, it is important to determine the level of physical activity connected with daily habits including occupational activities. The main goal of the presented study has been to assess the level of activities of daily living in different age groups and its differentiation by season and working (WD) and non-working days (NWD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
3
18
0
1
Order By: Relevance
“…Those results are consistent with Raymond et al, where the average daily number of steps achieved by KTx patients was more than 9000 [19]. Crosssectional studies conducted on healthy populations indicate that without any motivational or interventional procedures, the level of pedometer-assessed PA is lower than recommended and depends on working or non-working days, as well as the season [20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Those results are consistent with Raymond et al, where the average daily number of steps achieved by KTx patients was more than 9000 [19]. Crosssectional studies conducted on healthy populations indicate that without any motivational or interventional procedures, the level of pedometer-assessed PA is lower than recommended and depends on working or non-working days, as well as the season [20].…”
Section: Discussionsupporting
confidence: 90%
“…Most studies on assessment of PA in post-transplantation patients are based on subjective methods using standardized or self-prepared questionnaires. Those methods are burdened with a large measurement error and are usually overestimated, which has been previously proven [20,21]. This observation is partially reflected in the research presented here, where the high percentage of completed questionnaires was overestimated and did not meet the validity criteria, so those results could not be subjected to statistical analysis.…”
Section: Discussionmentioning
confidence: 72%
“…These 26 studies were conducted in 18 different countries with a dominance of the USA with six contributions [ 16 , 20 , 23 , 24 , 27 , 53 ] and Canada with four [ 9 , 31 , 54 , 56 ]. Two studies were developed in countries as Japan [ 13 , 55 ] and Poland [ 17 , 44 ]. Other countries developed one as: France [ 59 ], Iceland [ 37 ], Lithuania [ 32 ], Netherlands [ 34 ], Qatar [ 5 ], South Korea [ 42 ] Sweden [ 45 ], and the United Kingdom [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Physical inactivity is a global problem [ 9 , 10 , 11 ] that generates a growing concern [ 5 ]. It contributes to the obesity epidemic [ 12 , 13 ], and increases morbidity and mortality rates in chronic diseases [ 5 , 14 , 15 , 16 , 17 , 18 ]. It is associated with disease exacerbations, increased pain, poorer health-related quality of life and prognosis, among others health outcomes [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitsui et al showed that male office workers in a rural area are more active on non-working days than on working days in the summer, with an inverse pattern in the winter season [25]. However, other studies conducted in urban areas have found different patterns, which showed that the level of PA is lower on non-working days than during working days and people’s participation in these activities are limited to professional work and daily living activities [26, 27]. These findings indicate that employment status is an important factor in assessing physical activity.…”
Section: Introductionmentioning
confidence: 99%